20 Years of Intellectual Capital Research: A Bibliometric Analysis - Sigit Hermawan; Eny Maryati; Dewi Andriani (Universitas Pendidikan Ganesha, 2021)
Intellectual Capital (IC) study began over 20 years ago. But little mapping of this study has been done. “How many IC articles have been published and cited?” This is vital for future IC research. This study's goal is to map 20 years of IC research bibliometrically. This is significant because IC has been shown to boost company performance, competitiveness, and welfare. Bibliometric analysis is used because it is quantifiable, objective, avoids potential subjective bias, and confirms expert opinions in the field of IC. The results showed 3993 IC articles between 2000-2020. English is the most extensively used language in publications, accounting for 95.04 percent. IC and competitive advantage, IC statement, and IC perspective are the most researched themes. Nick Bontis, James Guthrie, and John Dumay are the most prolific. This study's findings will be useful to future IC researchers.